The XVII Amendment’s impact to Economy, Politics, and European Immigration during Prohibition in the United States - Enriquez, Daniella J (The Toro Historical Review, 2023)
Prohibition occurred between the years 1920 to 1933. The United States Congress ratified the XVII amendment prohibiting the sale, manufacture, and transport of intoxicating liquors. During these years United States emerged from its involvement in World War I, experienced the Roaring Twenties, and felt the impact of the Great Depression. The era historically transformed the United States during the period of thirteen years. Upon the ratification of XVIII amendment, the Volstead Act became the enforcing mechanism of the law, Prohibition took effect within the United States on January 17, 1920. The economy, law enforcement and European immigration were all sectors uniquely affected during the Prohibition era in the United States. The United States government political fallout occurred because they believed the ratification would positively impact the country’s economy, however; the government lost tax revenues immediately after the tax on liquor sales halted. The law’s goal was to eliminate all liquor within the United States. The government did not expect illegal smuggling nor the establishment of a bootlegging industry. The closure of saloons led to an illegal development of underground speakeasies. Alcohol smugglers thrived, while the National Anti-Saloon League influenced distinguished members of Congress and the government with their use of “pressure politics.” The Treasury Department assigned a Prohibition Unit agency known as the Federal Bureau of Investigation to follow paper tracks and anonymous tips about speakeasies and illegal smuggling. The United States endowed Border Patrol with law enforcement authority allowing them to make arrests without warrants on any violation of immigration laws. Immigrants found opportunities sidestepping the law and built speakeasies to supplement their incomes. Germans, Italians, and Irish Americans were all targeted because of citizens preconceived prejudices against immigrants in the United States.